Telomeres in Plants and Humans: Not So Different, Not So Similar - Procházková Schrumpfová, Petra; Fojtová, Miloslava; Fajkus, Jiří (Cells, 2019)
Parallel research on multiple model organisms shows that while some principles of telomere biology are conserved among all eukaryotic kingdoms, we also find some deviations that reflect different evolutionary paths and life strategies, which may have diversified after the establishment of telomerase as a primary mechanism for telomere maintenance. Much more than animals, plants have to cope with environmental stressors, including genotoxic factors, due to their sessile lifestyle. This is, in principle, made possible by an increased capacity and efficiency of the molecular systems ensuring maintenance of genome stability, as well as a higher tolerance to genome instability. Furthermore, plant ontogenesis differs from that of animals in which tissue differentiation and telomerase silencing occur during early embryonic development, and the "telomere clock" in somatic cells may act as a preventive measure against carcinogenesis. This does not happen in plants, where growth and ontogenesis occur through the serial division of apical meristems consisting of a small group of stem cells that generate a linear series of cells, which differentiate into an array of cell types that make a shoot and root. Flowers, as generative plant organs, initiate from the shoot apical meristem in mature plants which is incompatible with the human-like developmental telomere shortening. In this review, we discuss differences between human and plant telomere biology and the implications for aging, genome stability, and cell and organism survival. In particular, we provide a comprehensive comparative overview of telomere proteins acting in humans and in Arabidopsis thaliana model plant, and discuss distinct epigenetic features of telomeric chromatin in these species.
Keywords: stárnutí buněk; Plants; telomere; telomerasa; Arabidopsis; epigenetics; epigeneze genetická; review; Cellular Senescence; chromatin; rostliny; human; Chromatin; lidé; Telomerase; telomerase; Humans; telomery; aging; Telomere; Epigenesis, Genetic